Behavioral Finance in Investor Decision on Investment – A Study on Investor Perspective - Dr. Rajendra Prasad G R (International Journal on Economics, Finance and Sustainable Development, 2022)
This study is to analyze and understand the investment behavior and preferences of investors and their awareness about products and services provided by the company. Beings that are rational with focus on maximizing their returns but this assumption is flawed as we are here ignoring the biases, emotions, perceptions and other behavioral processes that affect the decisions of investors. Behaviour finance is still a new field of study in India whereas many studies are going on and have been done abroad. This article makes an attempt to compile the theoretical results of some Indian behavioral finance studies and throw light on the behaviour biases present in investors. The study attempts to analyze the behavior of investors towards investment pattern and to analyze the factors which an investor takes into consideration while taking Investment decision. The Study concludes that behavior matters a lot when it comes to making a wise investment decision on expected returns.